Improving ethical assurance for non-university researchers in crisis settings: an early vision based on democratic norms - Leanne Cochrane; Orla Drummond; Eliza Jordan (Research Ethics Review)
This article aims to open a discussion on better ethical assurance for non-university research actors drawing on democratic norms. It derives from the author’s experience of a gap in ethical assurance for social science and humanities (SSH) research that takes place outside academia, for example within international organisations, public bodies, non-governmental organisations (NGOs) and by private entities. Many of these actors commission, conduct or sub-contract research activities involving human participants on a regular basis, an activity that often increases during times of crisis where researchers in both the public and private sphere scramble to generate the new knowledge necessary to respond and prevent further harms. The ethical assurance frameworks for such research, while growing, remain limited. Discussion of research conducted by actors outside of university settings and their ethical assurance frameworks are both subjects under-interrogated within the literature. This paper seeks to open that discussion by presenting this broad non-university research context through the frame of research in crisis settings, where the ethical requirements of ‘do no harm’ and the ‘dual imperative’ possess an even heavier significance in research ethics. Furthermore, the global and diverse nature of crisis settings often gives rise to conversations concerning the positioning of the research actor and the need to empower the research participant. This paper presents an early vision of the non-university research actor and ethical assurance process based on the democratic norms of equality and inclusivity.